Necesidad de declarar la inconstitucionalidad del inciso tercero del art. 168 de la Ley Orgánica de Transporte, Tránsito y Seguridad Vial - Nagua, Juanito Alexander (2015)
This research work, entitled: " NEED TO DECLARE UNCONSTITUTIONAL THIRD PARAGRAPH OF ART. 168 ORGANIC LAW OF TRANSPORT , TRAFFIC AND ROAD SAFETY " is structured and developed in accordance with the provisions of Regulation graduation force at the National University of Loja. The generale objective raised in this investigation was: Conduct a critical, doctrinal and legal study of the Organic Law of Land Transport, Traffic and Road Safety in relation to oral and public hearing of prosecution. The methods applied for the implementation of this research work were: Scientific, Inductive, Analytic-Synthetic, Scientist. The techniques and instruments used was the survey of lawyers and doctors of jurisprudence and literature review of legal instruments. With the implementation of the survey concludes that:. 100% of respondents state that the 168-third paragraph Art of ORGANIC LAW OF TRANSPORTATION, TRAFFIC AND ROAD SAFETY is unconstitutional and warrants that the State through the National Assembly socialize the reform bill